A Multidrug Resistance Plasmid pIMP26, Carrying bla(IMP-26), fosA5, bla(DHA-1), and qnrB4 in Enterobacter cloacae - Wang, Su (Sci Rep, 2019)
IMP-26 was a rare IMP variant with more carbapenem-hydrolyzing activities, which was increasingly reported now in China. This study characterized a transferable multidrug resistance plasmid harboring bla(IMP-26) from one Enterobacter cloacae bloodstream isolate in Shanghai and investigated the genetic environment of resistance genes. The isolate was subjected to antimicrobial susceptibility testing and multilocus sequence typing using broth microdilution method, Etest and PCR. The plasmid was analyzed through conjugation experiments, S1-nuclease pulsed-field gel electrophoresis and hybridization. Whole genome sequencing and sequence analysis was conducted for further investigation of the plasmid. E. cloacae RJ702, belonging to ST528 and carrying bla(IMP-26), bla(DHA-1), qnrB4 and fosA5, was resistant to almost all β-lactams, but susceptible to quinolones and tigecycline. The transconjugant inherited the multidrug resistance. The resistance genes were located on a 329,420-bp IncHI2 conjugative plasmid pIMP26 (ST1 subtype), which contained trhK/trhV, tra, parA and stbA family operon. The bla(IMP-26) was arranged following intI1. The bla(DHA-1) and qnrB4 cluster was the downstream of ISCR1, same as that in p505108-MDR. The fosA5 cassette was mediated by IS4. This was the first report on complete nucleotide of a bla(IMP-26)-carrying plasmid in E. cloacae in China. Plasmid pIMP26 hosted high phylogenetic mosaicism, transferability and plasticity.